Effect of Mechanical Harvesting Technology Type and Harvester Ownership and Services Acquisition Methods on Profitability of Wild Blueberry Production - Emmanuel K. Yiridoe; Ahmad H. Khan; Travis J. Esau; Prosper S. Koto; Qamar U. Zaman (International Journal of Fruit Science, 2023)
ABSTRACTThe profitability of wild blueberry (Vaccinium angustifolium) production using two alternative mechanical harvesters was evaluated under three different harvester ownership/service arrangements commonly used by farmers. Production data for the economic analysis were obtained from on-farm trials conducted in Nova Scotia, Canada. Net returns were CAD$323 ha−1 using a semi-automatic bin handling system compared with CAD$281 ha−1 for a small box handling system with outright harvester purchase. By comparison, net returns were CAD$90 ha−1 using the semi-automatic bin handling system and CAD$63 ha−1 using the small box system using rental harvesting services. The results are more sensitive to changes in yield than price.